EFEKTIVITAS PELAKSANAAN PENGEMBANGAN PROGRAM USAHA MIKRO KECIL DAN MENENGAH KABUPATEN KUDUS - Erika Ningrum Sari; Mochammad Mustam (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Micro, small, medium enterprises or commonly known as UMKM is an independent productive economy national program, conducted by individuals without any constraints on other business companies. Many of UMKM doesn’t handled by the related office as the consequence of the huge amount of UMKM in Kudus regency. The Department of Manpower, Industry, Cooperatives and UMKM of Kudus regency runs the program in accordance with the planned programs and activities that are developed on the Renstra on the program by developing the small and micro enterprises due to improving the prosperity of the people in Kudus regency. The development program for the small and micro enterprises which was undertaken by the government attracted the writer to undergo a research that whether the development of umkm has been effective or not effective yet. The purpose of this study is to determine whether the development of umkm conducted by Disnakerperinkopukm Kudus has been effective or not. Researchers used 4 aspects to measure the effectiveness of the development of UMKM program in Kudus regency identified from the productivity, motivation, adaptation and integrity. The method used in this research is descriptive qualitative method. The result of this research shows that Disnakerperinkopukm of Kudus Regency in conducting empowerment through the umkm development is optimal, while there are some aspects that not optimal yet, it is related to the procurement of minimum training quota and the uneffective socialization. Recommendations gained from the research are; increasing the quota for business development training and socialization related to government policy about UMKM.